Lattice Waves in Two-Dimensional Hexagonal Quantum Plasma Crystals - 孙晓霞 王春华 高峰 (Chinese physics letters, 2010)
Lattice waves including a longitudinal wave and a transverse wave in two-dimensional hexagonal quantum plasma crystals are investigated by using the modified Debye-Hückel screening potential. It is shown that there exists an unstable region of lattice parameters, where the system will melt. The general dispersion relations are derived, and the waves propagating parallel to a primitive translation vector are discussed. We find that both the longitudinal and transverse waves are acoustic-like, and the longitudinal wave has a greater sound speed than that of the transverse wave in the long wavelength limit region.